Deconstructing Bias and Reconstructing Solutions: Theologizing the Notion of Justice as a Response to Gender Oppression. (May 2017) - Gray, Susan
The conclusion of Marcella Althaus-Reid and Lisa Isherwood's 2007 book, Controversies in Feminist Theology, noted that 'The future of feminist theologies are assured while gender and sexual oppression exist'. 1 Yet, they also spoke of a number of challenges to the field, specifically difference in methodologies, varied nomenclature and terminologies, and stereotyping among its practitioners. I would add another: that the nature of bias itself is not uniform nor homogeneous but is largely treated as such by contextual theologians. In this article the challenge presented by the presupposition that 'a bias-is-a-bias' is addressed from an epistemological one that attempts to delve into the nature(s) of bias, beginning with the question: if the root nature of the problem, that is bias, is not homogeneous but rather reflects the interplay of different types of biases, does not gender oppression call for more comprehensive solutions beyond solidarity or justice? While justice-based solutions (e.g. the dismantling of oppressive power structures) called for by feminist theologies are certainly valid and necessary, perhaps they function more as short-term solutions to a much larger dialectic, one that requires a more comprehensive grace-based approach. This article explores this idea and humbly offers a few methodological reflections.